A Highly Sensitive Refractometric Sensor Based on Cascaded SiN Microring Resonators - Daniel Pergande; Martin Weiland; Peter Lützow; Vanessa Zamora (Sensors, 2013)
We investigate a highly sensitive optical sensor based on two cascaded microring resonators exploiting the Vernier effect. The architecture consists of two microrings with a slight difference in their free spectral ranges. This allows the generation of the Vernier effect for achieving ultra-high sensitivities. The sensor chip was fabricated using a silicon nitride platform and characterized with isopropanol/ethanol mixtures. A sensitivity of 0.95 nm/% was found for isopropanol concentrations in ethanol ranging from 0% to 10%. Furthermore, a collection of measurements was carried out using aqueous sodium chloride (NaCl) in solutions of different concentrations, confirming a high sensitivity of 10.3 nm/% and a bulk refractive index sensitivity of 6,317 nm/RIU. A limit of detection of 3.16 ´ 10−6 RIU was determined. These preliminary results show the potential features of cascaded silicon nitride microring resonators for real-time and free-label monitoring of biomolecules for a broad range of applications.